DEF6 has potential to be a biomarker for cancer prognosis: A pan-cancer analysis - Yuan, Ziming; Zhong, Yuchen; Hu, Hanqing; Zhang, Weiyuan; Wang, Guiyu (Frontiers in Oncology, 2023)
DEF6 is a gene associated with the immune system and is thought to play a crucial role in autoimmunity. There are few DEF6-related studies in cancer, and it is assumed that DEF6 is a proto-oncogene. There is currently no pan-cancer analysis of DEF6, and we performed a systematic and comprehensive pan-cancer analysis of DEF6 in an attempt to reveal its role and function in cancer. Our results revealed that DEF6 is commonly aberrantly expressed in cancer and its expression is strongly correlated with survival prognosis in a variety of cancer types. By correlation analysis, we found that DEF6 was associated with multiple immune genes and was closely related to immune infiltration. In the enrichment analysis, DEF6 may have cross-talk with multiple cancer pathways and exert oncogenic or pro-cancer functions. In addition, we collected pathological samples from colorectal cancer patients for immunohistochemical analysis and found that patients with higher immunohistochemical scores had more lymph node metastases, higher CA199, and bigger tumor size. Overall, DEF6 is closely related to cancers and has the potential to act as a cancer biomarker.